Changes in Precipitation From North Atlantic Tropical Cyclones Under RCP Scenarios in the Variable‐Resolution Community Atmosphere Model. Issue 12 (13th June 2020) - Stansfield, Alyssa M.; Reed, Kevin A.; Zarzycki, Colin M.
Abstract: Decreasing climate models' grid spacing improves the representation of tropical cyclones at decadal time scales. In this study, a variable‐resolution (VR) version of the Community Atmosphere Model 5 (CAM5‐VR) is utilized to study North Atlantic tropical cyclone climatology in ensemble historical climate simulations and under two Representative Concentration Pathway (RCP) projections (RCP4.5 and RCP8.5). Basin‐wide tropical cyclone counts decrease in the RCP simulations, although landfalling storm counts do not show as straightforward of a pattern, especially when focusing on regional changes. Lifetime maximum intensity metrics suggest that tropical cyclones increase in strength in the RCP ensembles. However, despite increases in tropical cyclone‐related precipitation rates and the amount of precipitation produced per storm with warming, the annual average Rx5day from tropical cyclones over the eastern United States decreases due to less landfalling storms. This work is part of a continued effort to quantify how tropical cyclone‐induced hazards may change in future climates. Plain Language Summary: Landfalling tropical cyclones create dangerous conditions for residents of the eastern United States through heavy rainfall, strong winds, and storm surge. This work utilizes a global climate model to estimate how these hazards from such storms might change in the future by studying changes in the tropical cyclones' intensities, sizes, and rainfall accumulations. In these climate model simulations, the number of tropical cyclones in the North Atlantic decreases and so does the number of tropical cyclones that make landfall in the United States in the future climate projections. The average intensities of these storms increase. The rainfall intensities within the tropical cyclones also increase in the future climate projections, so that the amount of rainfall produced per storm increases. Based on our simulations, although the number of tropical cyclones that make landfall in the United States will decrease in the future, the amount of precipitation that each landfalling storm produces will increase. Key Points: North Atlantic tropical cyclone frequency decreases and median intensity increases in future CAM5 climate change projection simulations Due to less tropical cyclone landfalls in the United States, tropical cyclone precipitation over land decreases in CAM5 in the future Higher precipitation rates in future climate projections increase the amount of precipitation produced per hour of tropical cyclone impact